👤
a fost răspuns

AJUTOOOR!
Descompuneti in factori a unor expresii algebrice:
a) x³-2x²+x-2
b)x³-x²-4x+4
c)x³-7x+6
d)x³+2x²-4x-8



Răspuns :

a) x³-2x²+x-2 = x²(x-2)+(x-2)= (x-2)(x²+1)

b) 
x³-x²-4x+4 = x²(x-1)-4(x-1) = (x-1)(x²-4)=(x-1)(x²-2²)= (x-1)(x-2)(x+2)

c) 
x³-7x+6 = x³-x-6x+6= x(x²-1) -6(x-1) =  x(x-1)(x+1) -6(x-1) = (x-1)(x(x+1)-6) =
= (x-1)(x²+x-6) = (x-1)(x²+3x-2x-6)= (x-1)[x(x+3)-2(x+3)] = (x-1) (x-2) (x+3)

d) x³+2x²-4x-8 = x²(x+2)-4(x+2) = (x+2)(x²-4) = (x+2)(x²-2²)= (x+2)(x-2)(x+2) =
 = (x-2)(x+2)²
a) x³ - 2x² + x - 2 = ( x³ - 2x²) + ( x - 2)
                           = x²( x - 2) + ( x - 2)
                           = ( x - 2)( x² + 1)
b) x³ - x² - 4x + 4 = ( x³ - x²) - ( 4x - 4)
                           = x² ( x - 1) - 4( x - 1)
                           = ( x - 1)( x² - 4)
                           = ( x - 1)( x - 2)( x + 2)
c) x² - 7x + 6 = x² - x - 6x  + 6
                     = ( x² - x) - ( 6x - 6)
                     = x( x - 1) - 6( x - 1)
                     = ( x - 1)( x - 6)
d) x³ + 2x² - 4x - 8 = ( x³ + 2x² ) - ( 4x + 8)
                            = x² ( x - 2) - 4( x - 2)
                            = ( x - 2)( x² - 4)
                           = ( x - 2)( x - 2)( x + 2)
                           = ( x - 2)²(x + 2)
Sper ca ti-am fost de ajutor!